2017
DOI: 10.1109/jsac.2017.2699098
|View full text |Cite
|
Sign up to set email alerts
|

Coverage Analysis for Millimeter Wave Networks: The Impact of Directional Antenna Arrays

Abstract: Abstract-Millimeter wave (mm-wave) communications is considered a promising technology for 5G networks. Exploiting beamforming gains with large-scale antenna arrays to combat the increased path loss at mm-wave bands is one of its defining features. However, previous works on mm-wave network analysis usually adopted oversimplified antenna patterns for tractability, which can lead to significant deviation from the performance with actual antenna patterns. In this paper, using tools from stochastic geometry, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
165
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(166 citation statements)
references
References 32 publications
1
165
0
Order By: Relevance
“…It is shown that cooperation among randomly located BSs can effectively increase the coverage probability. By using tools from stochastic geometry, a general and tractable framework for coverage analysis with arbitrary distributions for interference power and arbitrary antenna patterns was developed and applied to mmWave ad hoc networks exploiting directional antenna arrays in [245]. It is shown that the coverage probabilities of mmWave ad hoc networks increase as a non-decreasing concave function with the antenna array size.…”
Section: Coverage and Connectivitymentioning
confidence: 99%
“…It is shown that cooperation among randomly located BSs can effectively increase the coverage probability. By using tools from stochastic geometry, a general and tractable framework for coverage analysis with arbitrary distributions for interference power and arbitrary antenna patterns was developed and applied to mmWave ad hoc networks exploiting directional antenna arrays in [245]. It is shown that the coverage probabilities of mmWave ad hoc networks increase as a non-decreasing concave function with the antenna array size.…”
Section: Coverage and Connectivitymentioning
confidence: 99%
“…It should be noted that all studies in [7]- [10] characterized the impacts of beamforming of antenna arrays based on the flat-top model. The sinc and cosine antenna models were used to analyze the impacts of antenna array size on coverage performance in [11]. Unfortunately, since the antenna models in [11] were too complicated, the analysis was limited to the scenarios in which each mobile station (MS) is assumed to be equipped with only one single antenna.…”
Section: Introductionmentioning
confidence: 99%
“…The sinc and cosine antenna models were used to analyze the impacts of antenna array size on coverage performance in [11]. Unfortunately, since the antenna models in [11] were too complicated, the analysis was limited to the scenarios in which each mobile station (MS) is assumed to be equipped with only one single antenna. Moreover, the analyses in [7]- [11] assumed the beam alignment to be perfect which is impossible for practical systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the model used for conventional sub-6 GHz systems where channel gain is obtained as the product of a Rayleigh or Nakagami-m random variable which accounts for small scale fading effect, and a path loss term that models the large scale fading effect. Similarly, a recent work on coverage analysis for mmWave line-of-sight (LOS) links with analog beamforming [6] approximates the beamformed directional channel by a random gain component based on the uniformly random single path (UR-SP) assumption. However, in non-LOS (NLOS) mmWave channels the power content of multi-path components [7] are comparable, and thus the modeling approaches considered for beamformed directional channels in existing literature are not applicable.…”
mentioning
confidence: 99%